`MIMIO TEACH` UNTUK PEMBELAJARAN TEORI DAN PRAKTIK DI JURUSAN TEKNIK MESIN UNNES - Wahyudi, Wahyudi; Widayat, Widi; Widjanarko, Dwi (Rekayasa : Jurnal Penerapan Teknologi dan Pembelajaran, 2016)
The Mechanical Engineering Department of Universitas Negeri Semarang received teaching aid grantin 2012 in the form of the “MimioTeach” consisting of MimioView, MimioPad and MimioTouch. However, until now the equipment has not been used optimally due to the lack of training. ”MimioTeach” is rich in features that can simplify the interactive teaching. The objectives of community service were: 1) introducing”MimioTeach”equipment consisting of Mimio Teach, Mimio Pad, Mimio View to the Lecturers of the Mechanical EngineeringDepartment, 2) trainingthe use of such equipment to the Lecturers of the Mechanical EngineeringDepartment, and 3) assisting Lecturers in using the equipment during their teaching proceess. The method of implementation was a training to use the equipmentduring the teaching proceess of the participants. The subjects of this training weretwenty lecturersof Mechanical Engineering. The results of the activities were 16 lecturers attended the Mimio Teach training in the Mechanical Engineering Department, Universitas Negeri Semarang. Participants were introduced to Mimio devices, were trained how to use it and were guided to operate the Mimio device independently. During the training the participants enthusiastically listened to and watched the demonstration of the use of instructional tools. Participants also asked about things that did not understand. When practical activities, the participants were proven to be able to operate the Mimiodevice. However, a continuous exercise is required to be more proficient.